AB0628 Lung Cancer in Systemic Sclerosis: Cases in A Hospital Cohort. (15th July 2016) - Corzo, P.; Pros, A.; Polino, L.; Balcells, E.
Abstract : Background: Systemic sclerosis (SS) is a rare disease that leads to greater morbidity and mortality than in general population, but due to its unfrequency there are very few clinical and epidemiological data. Some meta-analysis 1 about the increased incidence of cancer in SS compared to the average population (Relative risk (RR) 1.75 1 ) were published; even more relevant when it refers to lung cancer (RR 4.35 1 ), compared to the general population; suggesting that interstitial lung disease (ILD) may be the cause of this increased incidence Objectives: To provide our cases of lung cancer in patients with SS, describe the clinical, epidemiological and pathological features and assess the possible risk factors associated Methods: Retrospective review of lung cancer cases of a 115 patients hospital cohort with SS. Clinical and epidemiological characteristics, timeline, SS subtype, histology and likely associated risk factors are described. Results: The prevalence of cancer in our 115 patients serie with SS is 10.4% (12/115), lung cancer was the most frequent neoplasia (4/12, 33%) Case 1. Woman, 36 years old, nonsmoker, diagnosed at 23 year old of diffuse SS (DSS) Scl70+, with recurrent ulcers. ILD (HRCT and biopsy: desquamative interstitial pneumonia, DIP) at 29 years old. Treatment: prednisone (7.5 mg/ average dose), azathioprine 100mg, calcium antagonists, bosentan and alprostadil. She presented intercostal pain and was diagnosed by biopsy and HRCT of well defined adenocacinoma with mucosecretory pattern and acinar areas, T3N0M0. Pneumonectomy was performed with good results. Case 2. Woman, 72 years old, nonsmoker, diagnosed at 58 years old of DSS Scl70+ with recurrent ulcers and ILD (HRCT: nonspecific interstitial pneumonia, NSIP) at 64 years old. Treatment: calcium antagonists, bosentan and alprostadil. She presented abrupt clinical and PFT deterioration, biopsy and HRCT showed poorly differentiated non-small cell carcinoma T4N0M1b. Dyed six months after diagnosis. Case 3. Male, 47 years old, nonsmoker, diagnosed at 43 years old of DSS and ILD (HRCT: NSIP) with recurrent ulcers. Treatment: prednisone (7.5 mg/d), calcium antagonists, bosentan and alprostadil. He presented constitutional syndrome and respiratory clinical worsening, diagnosed by biopsy and HRCT of large cell neuroendocrine carcinoma of the lung, T3N0M1b. Stable after 18 months of palliative chemotherapy. Case 4. 57-years-old male, smoker, ESD diagnosis with rapid Raynaud's syndrome onset, HRCT and lung biopsy evidenced lung adenocarcinoma T2aN3M0. Improvement of skin symptoms after chemoradiation. Conclusions: Lung cancer is the most common malignancy in our cohort. All of them had DSS. Most of them (3/4) had a previous diagnosis of ILD and were nonsmokers, with a mean time of evolution from the SS diagnosis to neoplasia of 9.6 years and 6.3 years from diagnosis of ILD. The other case, had simultaneous diagnosis of SS and lung cancer. Only one case had been previously treated with non-steroid immunosuppressant. These results force us to strictly control the risk of neoplasia in patients with SS, predominantly those with diffuse involvement and ILD diagnosis. References: Martina Bonifazi et al. Systemic sclerosis (scleroderma) and cancer risk: systematic review and meta-analysis of observational studies. Rheumatology (Oxford). 2013;52:143–154 Disclosure of Interest: None declared